2012
DOI: 10.2174/156800912803251225
|View full text |Cite
|
Sign up to set email alerts
|

Polysialyltransferase: A New Target in Metastatic Cancer

Abstract: Polysialic acid (polySia) is a carbohydrate polymer critical for neuronal cell migration and axon pathfinding in embryonic development. Besides brain regions requiring persistent neuronal plasticity, polySia is essentially absent from the adult body. However, polySia is aberrantly re-expressed on many tumours, where it decorates the surface of NCAM (neuronal cell adhesion molecule) and modulates cell adhesion, migration and invasion. PolySia-NCAM expression is strongly associated with poor clinical prognosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 0 publications
2
113
0
Order By: Relevance
“…Increased sialylation in cancer also includes the expression of polysialic acid, which is associated with several types of cancers and is frequently expressed in high-grade tumours 51,52 . Polysialic acid can often be present in neural cell adhesion molecule 1 (NCAM1), and this is associated with aggressiveness and poor clinical outcome in cancers, including lung cancer, neuroblastoma and gliomas 51,52 .…”
Section: Sialylationmentioning
confidence: 99%
“…Increased sialylation in cancer also includes the expression of polysialic acid, which is associated with several types of cancers and is frequently expressed in high-grade tumours 51,52 . Polysialic acid can often be present in neural cell adhesion molecule 1 (NCAM1), and this is associated with aggressiveness and poor clinical outcome in cancers, including lung cancer, neuroblastoma and gliomas 51,52 .…”
Section: Sialylationmentioning
confidence: 99%
“…Its biosynthesis is regulated by polysialyltransferases. It has been found that polysialic acid is also aberrantly re-expressed on the surface of many tumors, where it plays a key role in disease progression and metastasis [34]. Therefore, polysialyltransferases have been also considered as an attractive anti-cancer drug target.…”
Section: Cytidine Analogsmentioning
confidence: 99%
“…From a clinical standpoint, changes in polySia expression have been observed in neurological disorders such as schizophrenia 9 . Likewise, polySia overexpression has been linked to the malignant potential of numerous tumors including neuroendocrine tumors, Wilms' tumor, neuroblastoma, colon cancer and pancreatic cancer 10 . However, despite these multifaceted roles in human biology and disease, the enzymes that mediate these critical posttranslational modifications, the polysialyl transferases, have remained uncharacterized at the molecular level.…”
mentioning
confidence: 99%